Effects of coral contact rate on the coral cover (pre and post Covid-19's pandemic movement control order) in Tunku Abdul Rahman Park, Malaysia / Nasrulhakim Maidin ... [et al.] - Maidin, Nasrulhakim; Manjaji-Matsumoto, B. Mabel; Asdari, M. Rafiee; Bavoh, Elvin Michael; Junsin, Noorannezza; Justine, Vanielie Terrence (Universiti Teknologi MARA, Perak, 2022)
Covid-19 pandemic lockdown has affected all activities worldwide, including the tourism sector in Tunku Abdul Rahman Park (TARP). This study has spanned since pre-MCO in July 2019, hence it can be investigated to observe the impact of tourism on coral cover, before and after the MCO. The study was conducted from July 2019 to July 2020 and divided into three intervals. A total of 4 permanent transect coral survey were carried out at every beginning of the interval and at the end of the study period. MCO that was enforced during Interval 3 (I3) recorded a significant drop of more than 90% in the number of visitors. Even with the drop in number of tourists, coral contact rate recorded a quite similar trend throughout the 3 interval ranging between 1.66 to 1.82. Coral cover in TARP after 1 year recorded an increase of 1.17%. The negative correlation between number of tourists and changes in coral cover proved that the concept of resting period is neded for coral reefs to recover from the constant stress and daily coral contact with visitors.